Preparation method and application of high-capacity activated carbon-based electrode material
By preparing hyperbranched polycarbonate polyurethane and potassium hydroxide and calcining, a high-capacity activated carbon-based electrode material is formed, which solves the problem of insufficient capacity of the negative electrode material of existing lithium-ion batteries and achieves higher specific capacity and cycle stability of the electrode material.
Patent Information
- Application Number
- CN202411834434.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The theoretical capacity of the negative electrode material of the existing lithium-ion battery is only 372mA·h/g, which limits the energy density of lithium-ion batteries. It is necessary to develop high-capacity activated carbon-based electrode materials for lithium-ion batteries.
Hyperbranched polycarbonate polyurethane was prepared by performing prepolymerization and hyperbranched chain extension reactions with polycarbonate diol, toluene-2,4-diisocyanate and hyperbranched chain extension agent, and blended with potassium hydroxide to form a high-capacity activated carbon-based electrode material.
This method improves the specific surface area and capacitance of activated carbon materials, forms a three-dimensional porous structure with richer pores, improves the charge and discharge specific capacity and capacity retention rate of the electrode materials, and has higher specific capacity and cycling stability.
Smart Images

Figure QLYQS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a preparation method and application of a high-capacity activated carbon-based electrode material. Background Art
[0002] As the global energy crisis intensifies, the development of green energy conversion and energy storage devices is imminent. Lithium-ion batteries have the advantages of high charge and discharge efficiency, high output voltage, good environmental performance, and wide operating temperature range. They have been widely used in new energy vehicles, notebooks, mobile phones and other equipment. The current commercial negative electrode material of lithium-ion batteries is graphite carbon negative electrode, and its theoretical capacity is only 372mA·h / g, which seriously limits the energy density of lithium-ion batteries. The development of new high-capacity activated carbon negative electrode materials for lithium-ion batteries is a research hotspot.
[0003] At present, activated carbon materials are mainly formed by high-temperature carbonization with biomass such as fruit shells, wood powder, and high-molecular polymers as precursors. Among them, high-molecular polymers have various types, can adjust the pores and specific surface area of the carbon matrix, and are convenient for introducing active heteroatoms such as nitrogen, phosphorus, and sulfur. They are widely used in electrode materials such as lithium-ion batteries and supercapacitors. Summary of the invention
[0004] Technical problem to be solved: The present invention provides a method for preparing an activated carbon-based electrode material for lithium-ion batteries having a high specific surface area and a high capacitance.
[0005] Technical solution: A method for preparing a high-capacity activated carbon-based electrode material, comprising the following steps: Step A, adding dry polycarbonate diol and diisocyanate into a reaction container, carrying out a prepolymerization reaction at 65-75° C. for 2-3 hours in a nitrogen atmosphere, then adding acetone and a hyperbranched chain extender, carrying out a hyperbranched reaction at 40-45° C. for 1.5-2 hours, and after the reaction, rotary evaporating the solution, washing with ethanol, and drying to obtain a hyperbranched polycarbonate polyurethane.
[0006] Step B: Grind and blend the hyperbranched polycarbonate polyurethane and potassium hydroxide, calcine in a tubular furnace, wash with water after cooling, and dry to obtain a high-capacity activated carbon-based electrode material.
[0007] In step A, the ratio of polycarbonate diol, diisocyanate and hyperbranched chain extender is 1 mol: (2.4-2.8) mol: (1.6-1.9) mol. The diisocyanate is toluene-2,4-diisocyanate or 4,4'-methylenebis(phenyl isocyanate).
[0008] Wherein, the preparation method of hyperbranched chain extender is: Step (1), add 1,4-dioxane, water, tris(2-aminoethyl)amine, 1,4-butane sultone, and sodium hydroxide to a reaction container, heat to 70-80°C, react for 5-8h, then add 1,4-butane sultone, wherein the ratio of tris(2-aminoethyl)amine, 1,4-butane sultone, and sodium hydroxide is 1 mol: (3-3.3) mol: (3-3.3) mol, continue to react for 3-5h, cool, add hydrochloric acid solution dropwise to adjust the pH to 5-6, precipitate, filter, and dry to obtain a chain extender precursor.
[0009] Step (2), add ethanol, chain extender precursor in a ratio of 1 mol: (3-3.3) mol: (3-3.6) mol, 2-bromoethanol, and sodium hydroxide to a reaction vessel, heat to 40-60°C, react for 12-18 hours, distill under reduced pressure, wash with acetone, add the product to water, heat to evaporate, cool and crystallize to obtain a hyperbranched chain extender. The reaction formula is: .
[0010] Wherein, in step B, the ratio of hyperbranched polycarbonate polyurethane to potassium hydroxide is 1 g:(2-3) g.
[0011] Wherein, the heating rate during calcination in step B is 4-6°C / min, the temperature is raised to 700-800°C, and the temperature is kept for 2-3h.
[0012] (III) Technical effect: The present invention utilizes a novel hyperbranched chain extender containing sulfonate to react with polycarbonate and diisocyanate to obtain a hyperbranched polycarbonate polyurethane, which has a large molecular chain crosslinking density and good carbonization property. After carbonization, it can form a three-dimensional porous structure with richer pores, which is beneficial to improve the specific carbonization rate, pore volume and surface area. At the same time, the molecular chain contains a large amount of sulfonate structure, which can accelerate the thermal decomposition of polycarbonate in the molecular chain, promote the isomerization and crosslinking of polycarbonate to form carbon, and further improve the carbonization rate, thereby carbonizing to form a porous activated carbon material with better electrochemical properties.
[0013] The hyperbranched polycarbonate polyurethane of the present invention contains a large amount of nitrogen and sulfur elements, and forms nitrogen-sulfur co-doped porous activated carbon after high-temperature carbonization, generating active sites such as pyrrole nitrogen, pyridine nitrogen, and thiophene sulfur, which are beneficial to improving electrical conductivity, improving pore structure, and increasing lithium storage sites. The porous structure is beneficial to promoting the transmission of lithium ions and electrons, thereby improving the charge and discharge specific capacity and capacity retention rate of the electrode material, and having better specific capacity and cycle stability. DETAILED DESCRIPTION
[0014] In order to make the purpose, technical solutions and advantages of the present disclosure clearer, the technical solutions of the present disclosure will be clearly and completely described below in combination with the embodiments of the present disclosure. Obviously, the described embodiments are only part of the embodiments of the present disclosure, rather than all of the embodiments.
[0015] Embodiment 1: (1) Add 120 mL of 1,4-dioxane, 20 mL of water, 40 mmol of tris(2-aminoethyl)amine, 80 mmol of 1,4-butane sultone, and 120 mmol of sodium hydroxide into a reaction vessel, heat to 70°C, react for 8 h, then add 46 mmol of 1,4-butane sultone, continue to react for 5 h, cool, add hydrochloric acid solution dropwise to adjust the pH to 5, precipitate, filter, and dry to obtain a chain extender precursor.
[0016] (2) Add 200 mL of ethanol, 40 mmol of chain extender precursor, 120 mmol of 2-bromoethanol, and 132 mmol of sodium hydroxide into a reaction vessel, heat to 50°C, react for 18 hours, distill under reduced pressure, wash with acetone, add the product to water, heat to evaporate, cool and crystallize to obtain a hyperbranched chain extender.
[0017] (3) Add 30 mmol of dry polycarbonate diol (molecular weight 1000) and 78 mmol of 4,4'-methylenebis(phenyl isocyanate) into a reaction container, and carry out a prepolymerization reaction at 65°C in a nitrogen atmosphere for 3 hours. Then, add 40 mL of acetone and 48 mmol of a hyperbranched chain extender, and carry out a hyperbranching reaction at 40°C for 2 hours. After the reaction, the solution is rotary evaporated, washed with ethanol, and dried to obtain a hyperbranched polycarbonate polyurethane.
[0018] (4) Grind and blend 10 g of hyperbranched polycarbonate polyurethane and 25 g of potassium hydroxide, heat to 700 °C in a tube furnace at a heating rate of 5 °C / min, calcine for 3 h, cool, wash with water, and dry to obtain a high-capacity activated carbon-based electrode material, weigh it, and calculate the carbonization rate. Carbonization rate = (mass before carbonization - mass after calcination and carbonization) ÷ mass before carbonization × 100%.
[0019] Embodiment 2: (1) Add 150 mL of 1,4-dioxane, 30 mL of water, 40 mmol of tris(2-aminoethyl)amine, 80 mmol of 1,4-butane sultone, and 132 mmol of sodium hydroxide into a reaction vessel, heat to 75°C, react for 5 h, then add 40 mmol of 1,4-butane sultone, and continue to react for 5 h. After cooling, add hydrochloric acid solution dropwise to adjust the pH to 6, precipitate, filter, and dry to obtain a chain extender precursor.
[0020] (2) Add 300 mL of ethanol, 40 mmol of chain extender precursor, 132 mmol of 2-bromoethanol, and 144 mmol of sodium hydroxide into a reaction vessel, heat to 40°C, react for 18 hours, distill under reduced pressure, wash with acetone, add the product to water, heat to evaporate, cool and crystallize to obtain a hyperbranched chain extender.
[0021] (3) Add 30 mmol of dry polycarbonate diol (molecular weight 1000) and 84 mmol of 4,4'-methylenebis(phenyl isocyanate) into a reaction container, and carry out a prepolymerization reaction at 70°C in a nitrogen atmosphere for 3 h. Then, add 40 mL of acetone and 57 mmol of a hyperbranched chain extender, and carry out a hyperbranching reaction at 45°C for 1.5 h. After the reaction, the solution is rotary evaporated, washed with ethanol, and dried to obtain a hyperbranched polycarbonate polyurethane.
[0022] (4) Grind and blend 10 g of hyperbranched polycarbonate polyurethane and 20 g of potassium hydroxide, heat the mixture to 750 °C at a heating rate of 5 °C / min in a tubular furnace, and calcine for 3 h. After cooling, wash with water, and dry to obtain a high-capacity activated carbon-based electrode material. The material is weighed and the carbon yield is calculated.
[0023] Embodiment 3: (1) Add 120 mL of 1,4-dioxane, 20 mL of water, 40 mmol of tris(2-aminoethyl)amine, 80 mmol of 1,4-butane sultone, and 132 mmol of sodium hydroxide into a reaction vessel, heat to 80°C, react for 5 h, then add 52 mmol of 1,4-butane sultone, continue to react for 3 h, cool, add hydrochloric acid solution dropwise to adjust the pH to 6, precipitate, filter, and dry to obtain a chain extender precursor.
[0024] (2) Add 300 mL of ethanol, 40 mmol of chain extender precursor, 120 mmol of 2-bromoethanol, and 120 mmol of sodium hydroxide into a reaction vessel, heat to 60°C, react for 12 h, distill under reduced pressure, wash with acetone, add the product to water, heat to evaporate, cool and crystallize to obtain a hyperbranched chain extender.
[0025] (3) Add 30 mmol of dry polycarbonate diol (molecular weight 1000) and 72 mmol of toluene-2,4-diisocyanate into a reaction container, and carry out a prepolymerization reaction at 75°C for 2 h in a nitrogen atmosphere. Then, add 30 mL of acetone and 48 mmol of a hyperbranched chain extender, and carry out a hyperbranching reaction at 40°C for 2 h. After the reaction, the solution is rotary evaporated, washed with ethanol, and dried to obtain a hyperbranched polycarbonate polyurethane.
[0026] (4) Grind and blend 10 g of hyperbranched polycarbonate polyurethane and 30 g of potassium hydroxide, heat the mixture to 800 °C at a heating rate of 5 °C / min in a tubular furnace, and calcine for 2 h. After cooling, wash the mixture with water, and dry it to obtain a high-capacity activated carbon-based electrode material. The material is weighed and the carbon yield is calculated.
[0027] Comparative Example 1: (1) Add 30 mmol of dry polycarbonate diol (molecular weight 1000) and 78 mmol of 4,4'-methylenebis(phenyl isocyanate) into a reaction container, and carry out a prepolymerization reaction at 65°C for 3 h in a nitrogen atmosphere. Then, add 40 mL of acetone and 48 mmol of 1,4-butanediol, and carry out a hyperbranching reaction at 40°C for 2 h. After the reaction, the solution is rotary evaporated, washed with ethanol, and dried to obtain a hyperbranched polycarbonate polyurethane.
[0028] (2) Grind and blend 10 g of hyperbranched polycarbonate polyurethane and 25 g of potassium hydroxide, heat the mixture to 700 °C at a heating rate of 5 °C / min in a tubular furnace, and calcine for 3 h. After cooling, wash the mixture with water, and dry it to obtain an activated carbon-based electrode material. The material is weighed and the carbon yield is calculated.
[0029] Comparative Example 2: (1) Add 30 mmol of dry polycarbonate diol (molecular weight 1000) and 78 mmol of 4,4'-methylenebis(phenyl isocyanate) into a reaction vessel, and carry out a prepolymerization reaction at 65°C for 3 h in a nitrogen atmosphere. Then, add 40 mL of acetone and 48 mmol of trimethylolpropane ( ), and a hyperbranching reaction was carried out at 40° C. for 2 h. After the reaction, the solution was rotary evaporated, washed with ethanol, and dried to obtain a hyperbranched polycarbonate polyurethane.
[0030] (2) Grind and blend 10 g of hyperbranched polycarbonate polyurethane and 25 g of potassium hydroxide, heat the mixture to 700 °C at a heating rate of 5 °C / min in a tubular furnace, and calcine for 3 h. After cooling, wash the mixture with water, and dry it to obtain an activated carbon-based electrode material. The material is weighed and the carbon yield is calculated.
[0031] Comparative Example 3: (1) Add 30 mmol of dry polycarbonate diol (molecular weight 1000) and 78 mmol of 4,4'-methylenebis(phenyl isocyanate) into a reaction vessel, and carry out a prepolymerization reaction at 65°C for 3 h in a nitrogen atmosphere. Then, add 40 mL of acetone and 48 mmol of sodium 1,2-dihydroxy-3-propanesulfonate ( ), and a hyperbranching reaction was carried out at 40°C for 2 hours. After the reaction, the solution was rotary evaporated, washed with ethanol, and dried to obtain polycarbonate polyurethane.
[0032] (2) Grind and blend 10 g of polycarbonate polyurethane and 25 g of potassium hydroxide, heat the mixture to 700 °C at a heating rate of 5 °C / min in a tubular furnace, and calcine for 3 h. After cooling, wash with water, and dry to obtain an activated carbon-based electrode material. The material is weighed and the carbon yield is calculated.
[0033] The pore volume and specific surface area of the carbon-based electrode material were determined by nitrogen adsorption-desorption method using a specific surface area and porosity analyzer. The electrode material was vacuum degassed at 150°C for 12 h before testing.
[0034] Table 1 Carbonization rate, pore volume and specific surface area test Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Carbonization rate (%) 11.4 16.7 14.9 4.2 6.4 7.5 Pore volume (cm3 / g) 0.732 0.581 0.836 0.407 0.680 0.436 Specific surface area (m2 / g) 985.8 824.9 1135.2 585.7 913.6 604.5 Activated carbon-based electrode material, conductive carbon black and polyvinylidene fluoride were added to N-methylpyrrolidone in a mass ratio of 8:1:1. After mixing, the slurry was evenly coated on the surface of copper foil and dried to make a working electrode. Metal lithium sheet was used as the negative electrode, 1 mol / L LiPF6 solution was used as the electrolyte (the solvent was ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a volume ratio of 1:1:1), and a glass fiber membrane was assembled into a button battery in an argon glove box. The battery testing system was used to carry out constant current discharge and charge performance tests with a voltage range of 0.1-3V and a current density of 0.1A / g.
[0035] Table 2 Charge and discharge performance test First cycle discharge capacity (mA·h / g) Discharge capacity after 100 cycles (mA·h / g) Capacity retention rate (%) Example 1 804.5 712.9 88.6 Example 2 627.8 579.0 92.2 Example 3 955.4 836.7 87.6 Comparative Example 1 512.6 376.9 73.5 Comparative Example 2 667.2 542.3 81.3 Comparative Example 3 585.0 451.7 77.2 After testing, the high-capacity activated carbon-based electrode materials prepared in each embodiment have higher carbonization rate, pore volume and specific surface area. This is because the hyperbranched polycarbonate polyurethane has a hyperbranched cross-linked network structure, a large cross-linking density, better carbonization, and a three-dimensional porous structure with richer pores can be formed after carbonization, which is beneficial to improve the specific carbonization rate, pore volume and surface area. At the same time, the molecular chain contains a large amount of sulfonate structure, which can accelerate the thermal decomposition of polycarbonate in the molecular chain, promote isomerization and cross-linking carbonization of polycarbonate, thereby further improving the carbonization rate, and can be carbonized to form a porous activated carbon material with better electrochemical performance. At the same time, the hyperbranched polycarbonate polyurethane contains a large amount of nitrogen and sulfur elements, and after high-temperature carbonization, nitrogen-sulfur co-doped porous activated carbon is formed, generating active sites such as pyrrole nitrogen, pyridine nitrogen, and thiophene sulfur, which is beneficial to improve electrical conductivity, improve pore structure, increase lithium storage sites, improve the specific capacity and cycle stability of electrode materials, and show higher charge and discharge specific capacity and capacity retention rate.
[0036] Compared with Example 1, Comparative Examples 1 and 3 use 1,4-butanediol and sodium 1,2-dihydroxy-3-propanesulfonate as chain extenders, and the obtained polycarbonate polyurethane is a linear molecular chain without a hyperbranched three-dimensional cross-linked structure, and the polycarbonate polyurethane of Comparative Example 1 also does not contain a sulfonate structure, resulting in small pore volume and specific surface area of the activated carbon after carbonization of the two, and low carbonization rate, and low charge and discharge specific capacity and capacity retention rate of the electrode material, and poor electrochemical performance.
[0037] Comparative Example 2 uses trimethylolpropane as a chain extender, and the obtained polycarbonate polyurethane does not contain sulfonate groups, has poor charring properties, and has a low charring rate. In addition, the charge and discharge specific capacity and capacity retention rate of the electrode material are low, and the electrochemical performance is poor.
Claims
1. A method for preparing a high-capacity activated carbon-based electrode material, characterized in that: The preparation method is as follows: Step A, add dry polycarbonate diol and diisocyanate into a reaction vessel, perform prepolymerization in a nitrogen atmosphere, and then add acetone, the structural formula is A hyperbranched chain extender is added to carry out a hyperbranching reaction, and after the reaction, the solution is rotary evaporated, washed with ethanol, and dried to obtain a hyperbranched polycarbonate polyurethane; Step B: Grind and blend the hyperbranched polycarbonate polyurethane and potassium hydroxide, calcine in a tubular furnace, wash with water after cooling, and dry to obtain a high-capacity activated carbon-based electrode material.
2. The method for preparing a high-capacity activated carbon-based electrode material according to claim 1, characterized in that: In the step A, the ratio of polycarbonate diol, diisocyanate and hyperbranched chain extender is 1 mol: (2.4-2.8) mol: (1.6-1.9) mol.
3. The method for preparing a high-capacity activated carbon-based electrode material according to claim 1, characterized in that: The diisocyanate is toluene-2,4-diisocyanate or 4,4'-methylenebis(phenyl isocyanate).
4. The method for preparing a high-capacity activated carbon-based electrode material according to claim 1, characterized in that: The preparation method of the hyperbranched chain extender is: Step (1), adding 1,4-dioxane, water, tris(2-aminoethyl)amine, 1,4-butane sultone and sodium hydroxide to a reaction vessel, heating to 70-80°C, reacting for 5-8h, then adding 1,4-butane sultone, continuing the reaction for 3-5h, cooling, adding hydrochloric acid solution dropwise to adjust the pH to 5-6, precipitating a precipitate, filtering and drying to obtain a chain extender precursor; Step (2), add ethanol, a chain extender precursor in a ratio of 1 mol: (3-3.3) mol: (3-3.6) mol, 2-bromoethanol, and sodium hydroxide into a reaction container, heat to 40-60° C., react for 12-18 hours, distill under reduced pressure, wash with acetone, add the product into water, heat to evaporate, cool and crystallize, and obtain a hyperbranched chain extender.
5. The method for preparing a high-capacity activated carbon-based electrode material according to claim 4, characterized in that: In the step (1), the ratio of tri(2-aminoethyl)amine, 1,4-butanesultone and sodium hydroxide is 1 mol: (3-3.3) mol: (3-3.3) mol.
6. The method for preparing a high-capacity activated carbon-based electrode material according to claim 1, characterized in that: In the step A, the prepolymerization reaction is carried out at 65-75° C. for 2-3 hours, and the hyperbranching reaction is carried out at 40-45° C. for 1.5-2 hours.
7. The method for preparing a high-capacity activated carbon-based electrode material according to claim 1, characterized in that: In the step B, the ratio of the hyperbranched polycarbonate polyurethane to potassium hydroxide is 1 g:(2-3) g.
8. The method for preparing a high-capacity activated carbon-based electrode material according to claim 1, characterized in that: The heating rate during calcination in step B is 4-6°C / min, the temperature is raised to 700-800°C, and the temperature is kept for 2-3h.
9. Use of a high-capacity activated carbon-based electrode material obtained by the preparation method according to any one of claims 1 to 8 in a lithium-ion battery.
Citation Information
Patent Citations
Preparation method and application of polyurethane-based porous carbon electrode material for supercapacitor
CN105702479A
Flexible lithium ion battery positive electrode piece and preparation method thereof
CN110010849A
Preparation process and application of hyperbranched polyester polyol
CN118546346A
Polyurethane resin and electrically conductive roll using the same
JP2006274139A